2002
DOI: 10.1152/ajpgi.00344.2001
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone regulates the activity and expression of the peptide transporter PEPT1 in Caco-2 cells

Abstract: An oligopeptide transporter (PEPT1) in the small intestine plays an important role in the absorption of small peptides and peptide-like drugs. We examined the effect of thyroid hormone 3,5,3′-l-triiodothyronine (T3) on the activity and expression of PEPT1 in human intestinal Caco-2 cells. Treatment of Caco-2 cells with T3 inhibited [14C]glycylsarcosine uptake in a time- and dose-dependent manner. [14C]glycylsarcosine uptake was reduced by pretreatment of the cells with 100 nM T3 for 4 days (67% of control valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…The reason for the increased renal clearance of digoxin is considered to be a facilitation of tubular secretion (Bonelli et al, 1978); however, the mechanisms underlying the altered pharmacokinetics of digoxin in thyroid disease have not been fully elucidated. Previous studies have shown that thyroid hormone regulates the expression levels of various membrane transporters such as the fructose transporter GLUT5 (Matosin-Matekalo et al, 1999), the peptide transporter PEPT1 (Ashida et al, 2002), Na ϩ /K ϩ -ATPase (Giannella et al, 1993), and the Na ϩ /H ϩ exchanger NHE1 . Therefore, we hypothesized that the alteration in the plasma concentration of digoxin in patients with thyroid disorders might be due to changes in Pgp expression by thyroid hormone.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the increased renal clearance of digoxin is considered to be a facilitation of tubular secretion (Bonelli et al, 1978); however, the mechanisms underlying the altered pharmacokinetics of digoxin in thyroid disease have not been fully elucidated. Previous studies have shown that thyroid hormone regulates the expression levels of various membrane transporters such as the fructose transporter GLUT5 (Matosin-Matekalo et al, 1999), the peptide transporter PEPT1 (Ashida et al, 2002), Na ϩ /K ϩ -ATPase (Giannella et al, 1993), and the Na ϩ /H ϩ exchanger NHE1 . Therefore, we hypothesized that the alteration in the plasma concentration of digoxin in patients with thyroid disorders might be due to changes in Pgp expression by thyroid hormone.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, molecular identification of PEPT1 and PEPT2 provided a novel opportunity to determine the mechanisms of their regulation. For example, it was reported that the intestinal PEPT1 is regulated by various factors, including dietary conditions (Ogihara et al, 1999;Shiraga et al, 1999;Naruhashi et al, 2002), hormones such as insulin, leptin, and thyroid hormone (Buyse et al, 2001;Ashida et al, 2002;Gangopadhyay et al, 2002), epidermal growth factor (Nielsen et al, 2001), development (Shen et al, 2001), and some pharmacological agents (Fujita et al, 1999;Berlioz et al, 2000).…”
mentioning
confidence: 99%
“…Moreover, although hyperplasia and increased uptake were evident even at 1 wk post-resection, cellular mRNA levels in the ileal enterocyte decreased 3-fold at 1 wk post-resection, while cellular protein levels remained unchanged. This decrease in gene expression of PepT1 despite the strong catabolic stress with a 70% proximal small bowel resection might be related to some counterregulatory hormones (such as epidermal growth factor and triiodothyronine) or other negative regulators of PepT1 gene expression as has been suggested by other in vitro studies (in cell cultures) [23][24]; however, we have no objective data to support this statement. Similar findings of a decrease in jejunal mRNA for PepT1 were reported after enterectomy in rabbits, but no protein or uptake studies were carried out [25].…”
Section: Discussionmentioning
confidence: 68%